2000
DOI: 10.1126/science.287.5450.138
|View full text |Cite
|
Sign up to set email alerts
|

A Mammalian H + Channel Generated Through Alternative Splicing of the NADPH Oxidase Homolog NOH-1

Abstract: Voltage-gated proton (H+) channels are found in many human and animal tissues and play an important role in cellular defense against acidic stress. However, a molecular identification of these unique ion conductances has so far not been achieved. A 191-amino acid protein is described that, upon heterologous expression, has properties indistinguishable from those of native H+ channels. This protein is generated through alternative splicing of messenger RNA derived from the gene NOH-1 (NADPH oxidase homolog 1, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 273 publications
(54 citation statements)
references
References 23 publications
0
54
0
Order By: Relevance
“…These novel currents were absent in cells from X-CGD patients, indicating that they required the gp91 phox molecule. The recognition that gp91 phox contains a proton channel motif (Starace et al, 1997) suggested that the flavocytochrome could function as a proton channel and led to the cloning of the NOX homologues (Bánfi et al, 2000). Heterologous expression of NOX homologues in HEK-293 and CHO cells generated proton currents that recapitulated the properties of endogenous proton currents (Bánfi et al, 2000;Maturana et al, 2001), validating the channel theory.…”
Section: And F)mentioning
confidence: 68%
See 1 more Smart Citation
“…These novel currents were absent in cells from X-CGD patients, indicating that they required the gp91 phox molecule. The recognition that gp91 phox contains a proton channel motif (Starace et al, 1997) suggested that the flavocytochrome could function as a proton channel and led to the cloning of the NOX homologues (Bánfi et al, 2000). Heterologous expression of NOX homologues in HEK-293 and CHO cells generated proton currents that recapitulated the properties of endogenous proton currents (Bánfi et al, 2000;Maturana et al, 2001), validating the channel theory.…”
Section: And F)mentioning
confidence: 68%
“…The recognition that gp91 phox contains a proton channel motif (Starace et al, 1997) suggested that the flavocytochrome could function as a proton channel and led to the cloning of the NOX homologues (Bánfi et al, 2000). Heterologous expression of NOX homologues in HEK-293 and CHO cells generated proton currents that recapitulated the properties of endogenous proton currents (Bánfi et al, 2000;Maturana et al, 2001), validating the channel theory. However, proton currents were not observed in COS-phox cells expressing a functional oxidase (Morgan et al, 2002), suggesting instead that the oxidase modulates a proton channel.…”
Section: And F)mentioning
confidence: 68%
“…(105). Nox1 is a homolog of Nox2 (5, 187). Immunocytochemical analysis revealed that Nox2 and Nox4 protein levels are increased in the cytosol and nuclei, respectively of glomus cells of IH-exposed carotid bodies (146).…”
Section: Mechanisms Underlying the Effects Of Ih On The Carotid Bodymentioning
confidence: 99%
“…phox (now renamed NOX2) generated nearly identical proton currents , while the expression of a truncated NOX1 protein containing only the first four transmembrane domains, but retaining the predicted H C channel motif, was sufficient to induce H C currents (Banfi et al 2000). Moreover, expression of the Ca 2C -activated oxidase NOX5, which contains four EF-hand domains in its N-terminus and is activated directly by Ca 2C , generated H C currents that were activated by an increase in the cytosolic free Ca 2C concentration .…”
Section: ) Expression In Hek-293 Cells Of Gp91mentioning
confidence: 99%